Palaeoenvironments and site formation processes at the Neolithic lakeside settlement of Dispilio, Kastoria, Northern Greece - Karkanas, P.; Pavlopoulos, K.; Kouli, K.; Ntinou, M.; Tsartsidou, G.; Facorellis, Y.; Tsourou, T. (Geoarchaeology, 2011)
Dispilio is a lakeside settlement by the Orestias Lake, Kastoria, northern Greece. The site was inhabited from the Middle Neolithic to the Chalcolithic, with some surface evidence of Bronze Age occupation. Microfacies analysis of the sediments, supported by a suite of environmental indices, has provided detailed paleoenvironmental data and elucidated the main processes involved in the formation of the site and its history of occupation. The settlement was established on the lakeshore, on a shallow sand ridge and a shore marsh. Initially, houses were built on raised platforms above the water. After a major conflagration, a range of depositional microenvironments were established that caused local changes in the sedimentation rate. Therefore, some areas quickly emerged and became dry land, while some others continued to be flooded as part of the transitional supra-littoral environment. On the dry land, houses were built directly on the ground, whereas in the transitional areas houses continued to be built on raised platforms. Thus, gradually, a mound was formed and further shaped by subsequent lake-level fluctuations. One of the lake-level rises is tentatively related to the abandonment of the mound in the Chalcolithic and the development of a hardpan on its surface. There is also evidence of later occupation during the Bronze Age in the form of a few, mostly surface, archaeological remains.